Avaliação in vitro do efeito da metformina no tratamento de câncer de mama triplo negativo - Guimarães, Isabella dos Santos (2013)
Triple-negative breast cancer (TNBC) is a heterogeneous and poor prognostic disease, partially due to its ineligibility to target therapy, and the high relapse index, despite the initial satisfactory response to antineoplastic drugs. Therefore, the identification of alternative substances is urgent, as herein presented with regard to metformina and TNBC (lineage MDAMB231). Despite the low percentage of apoptotic/necrotic cells induced by metformin, 4.1% (10 μM) e 8.8% (54 mM), there was a discrete increase of cells in sub-G0, which is in agreement with the low value, despite doubled, of apoptosis/necrosis induced by metformina 54 mM. Metformin reverted ERK constitutive activation, possible antineoplastic mechanism; however, only reduced cellular proliferation at high doses (10 μM vs. 54 mM, 9.8% vs. 45.23%, respectively), possibly due to the modulation of other mechanisms of action. Paclitaxel 0.25 μM induced apoptosis/necrosis in 29% of the cells, which is comparable to the 36.34% of dead cells obtained by MTT. Despite the cell cycle arrest in G2/M that favours its mechanism of action, its antineoplastic efficacy can be compromised by ERK constitutive activation, which is related to taxane chemoresistance. Metformin 10 μM combined with paclitaxel 0,25 μM, although synergic with regard to the antineoplastic effect (dead cells = 53.20%), kept constant the induction of apoptosis/necrosis when compared to paclitaxel alone, as the benefit of arresting the cell cycle at G2/M can be overcome by ERK constitutive activation. When administered at their IC50, metformin 54 mM and paclitaxel 0,25 μM, the percentage of apoptotic/necrotic cells increased to 41%, which is comparable to the decrease in cell proliferation (59.9% of dead cells). Worthwhile pointing that: i) ERK constitutive activation was reversed, favoring paclitaxel toxicity; ii) the number of cells in sub-G0 increased. Indeed, among the 41% apoptotic/necrotic cells, 21.4% derived from late apoptosis, thus justifying sub-G0 expansion. The data point to mutual synergism between metformina and paclitaxel. Our findings support that, among other mechanisms of action, metformina is an indirect inhibitor of ERK, possibly of mTOR as well, explaining, therefore, its potential application in the treatment of TNBC, a major challenge of clinical oncology.